(untitled) (Materiali di Estetica. Terza serie, 2022)
This essay explores the value of the artist’s action and the power that his work exercises in the socio-political history of his country. It talks about Picasso and his Guernica, offering a reading of the work following the thread of Antonio Banfi’s aesthetics through the critical look of Dino Formaggio. The scene opens with the parisian Expo of 1937. The article is then integrated with aesthetic, moral and civil contents that guide the reader to understand the concept of morality, crisis and life of the art for Banfi and the connection with Picasso’s cultural work, starting from his writings against Franco’s atrocities up to Guernica. An authentic reading of the work is inserted that wants to support the moral shock determined by Guernica: a real denunciation of the misery and corruption of the government, inciting the people to fight. Finally, in order to show how current the artists’ interest in social, political and international problems is, the essay ends by presenting the work of two particularly committed contemporary artists: the Italian Paola Ravasio and the Syrian Tammam Azzam.